PENGUATAN BRANDING DAN KAPASITAS POKDARWIS DALAM PENGEMBANGAN DESA WISATA SELUMBUNG YANG BERKELANJUTAN - I Made Trisna Semara; Ni Luh Putu Intan Nirmalasari; I Made Krisna Adi Chandra (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
Selumbung Tourism Village is one of the potential tourist destinations in Karangasem Regency, Bali, known for its rich natural resources, culture, and local traditions. However, in recent years, the village has faced several challenges, including a decline in tourist visits and a weak destination brand identity. These issues have been exacerbated by the lack of synergy in management among members of the Tourism Awareness Group (POKDARWIS) and limited capacity in managing digital promotion. In response to these problems, a community engagement program carried out by the Tourism Management Study Program aimed to strengthen destination branding and enhance the capacity of POKDARWIS members through digital marketing training, assistance in promotional content development, and revitalization of the group's vision and mission. The implementation was conducted through a participatory approach, including observation, focus group discussions (FGDs), training sessions, and result evaluations. The outcomes of the program indicated an increased understanding among POKDARWIS members regarding the importance of branding and digital marketing strategies, the development of a new promotional narrative for the village, and the formulation of a collaborative action plan. This activity has had a positive impact by fostering a spirit of togetherness, increasing the competitiveness of the destination, and reinforcing the sustainable development direction of Selumbung Tourism Village.